Dwujęzyczność a opóźnienie poznawczych objawów demencji - Jakoniuk-Diallo, Anna; Bączyk , Martyna (Studia Edukacyjne, 2021)
Bilingualism is a topic that is most often discussed in the context of raising and working with children. However, the role that bilingualism plays in adulthood and late adulthood is underestimated in the literature. At this stage of life, some people may develop the first symptoms of neurodegenerative diseases, mainly associated with memory and communication disorders. The article briefly introduces the most common causes of dementia symptoms and then discusses bilingualism in several, closely related aspects. The publication contains information on the impact of bilingualism on delaying the symptoms of dementia and triggers of this phenomenon. The creativity of bilinguals and the unique impact of bilingualism on working memory and executive control are addressed.